CONSTITUTIONAL GUARANTEES OF THE RIGHT OF INDIVIDUALS AND CITIZENS TO ENGAGE IN ENTREPRENEURSHIP IN UZBEKISTAN (World Bulletin of Management and Law, 2025)
The article provides a comprehensive analysis of the constitutional guarantees of the right of individuals and citizens to engage in entrepreneurship in the Republic of Uzbekistan. The role and significance of this right in economic activity, its specificity in the system of human rights, and the norms included in the new edition of the Constitution of the country to ensure the right to entrepreneurship are discussed. The article discusses the issues of the inviolability of private property rights, the role of the state in the development of market relations, and ensuring freedom of entrepreneurship based on legal guarantees of property ownership. Referring to international experience, the constitutional norms of such countries as Italy, Spain, and France are comparatively analyzed and their features in protecting entrepreneurial activity are outlined. In addition, specific proposals are made to further strengthen the legal foundations of entrepreneurial activity in Uzbekistan, improve the mechanisms for implementing constitutional norms in practice, and eliminate shortcomings in legislation